Two scales, one methodology: Expenditure based equivalence scales for the United States and Germany - Joachim Merz; Thesia Garner; Timothy M. Smeeding; Jürgen Faik; David Johnson (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1994)
Choosing an appropriate equivalence scale is a prerequisite for comparisons of economic well-being income distribution, inequality or poverty. This is true for country specific work or for cross-national comparisons. Researchers generally either use a country specific equivalence scale (social assistance, expert based, or poverty scales), or adopt a single scale for all comparison across countries. Here we follow a different approach. We use microdata to estimate equivalence scales based on a revealed preference consumption approach for West Germany and the United States. We review several approaches and rely on a complete demand system approach, which provides constant utility based equivalence scales using an extended linear expenditure system (ELES). The multiple equation expenditure system takes into account a full market basket with all its interdependencies and relative prices. Our consumption-based equivalence results are compared to alternative consumption based measures, expert based measures, and subjective based measures in use in both countries and to other scales used for cross-national comparisons. – – Die Wahl einer passenden Äquivalenzskala ist Voraussetzung für Vergleiche der Einkommensverteilung ökonomischer Wohlfahrt, Ungleichheit und Armut. Dies gilt vor allem für länderspezifische Analysen und/oder für länderübergreifende Vergleiche. Es werden von Forschern entweder eine jeweils landesspezifische Äquivalenzskala (Sozialhilfe, Experten basierte oder Armutsskalen) oder eine einzige Skala für einen mehrere Länder umfassenden Vergleich verwendet. Wir verfolgen hier einen unterschiedlichen Ansatz. Wir verwenden Mikrodaten um Äquivalenzskalen zu schätzen, die auf offenbarten Konsumpräferenzen für die alte Bundesrepublik und die Vereinigten Staaten basieren. Wir überprüfen verschiedene Ansätze und beziehen uns auf einen nachfragetheoretisch fundierten Systemansatz, der konstante nutzenbasierte Äquivalenzskalen über ein erweitertes lineares Ausgabensystem (ELES) liefert. Dieses multiple Ausgabegleichunmgssystem trägt einem vollen Warenkorb mit allen seinen Interdependenzen und relativen Preisen Rechnung. Unsere konsumbasierten Äquivalenzskalen werden mit alternativen Skalen, expertenbasierte und Skalen subjektiver individueller Einschätzung und anderen Skalen verglichen, die in beiden Ländern Verwendung finden und für länderübergreifende Vergleiche benutzt werden.
Keywords: I30; I32; D30; D31; 330; alternative equivalence scale; Germany; USA; distribution of income; inequality; poverty; Alternative Äquivalenzskalen; Deutschland; USA; Einkommensverteilung; Ungleichheit; Armut; Disparitätsmaß; Verbraucherausgaben; Offenbarte Präferenzen; Haushaltsbudget-Statistik; Deutschland; USA